EVOLUTION OF THE VALUES AND ECONOMIC STIMULUS IN RUSSIA (XIX-XXI cc.): TABLE OF CONTENTS, KEY STAGES. FACTORS OF DYNAMICS OF ENTREPRENEURSHIP AND BUSINESS IN RUSSIAN FEDERATION - S. Sazanova (Вестник университета)
The article studies the evolution of the value of Russian entrepreneurship and their interrelation with the incentives of economic management; identified the main stages of development, as well as the institutional, economic and other factors affecting the dynamics of business and entrepreneurial activity in Russia XIX-XX centuries.